Prophylactic effect of dexamethasone in reducing postoperative sore throat - Park, Sun-young (The Korean Society of Anesthesiologists, 2010)
BACKGROUND: This study was performed to compare the effectiveness of prophylactic dexamethasone and postintubation dexamethasone in reducing the incidence and severity of postoperative sore throat (POST). METHODS: This was a prospective, randomized, double-blind clinical trial. The study population consisted of 70 patients between 20 and 60 years old who were classified as American Society of Anesthesiologists I-II and were scheduled for elective laparoscopic cholecystectomy. The patients were divided randomly into two groups. Patients in the prophylactic and postintubation groups received intravenous injection of 10 mg of dexamethasone 30 min before or after tracheal intubation, respectively. The patients were interviewed 1, 6, and 24 h after the operation. The incidence and severity of POST were recorded. RESULTS: The severity scores of POST at 1 and 6 h after the operation were significantly lower in the prophylactic group than in the postintubation group. There were no significant differences in the incidence of POST during the 24 h after the operation between the two groups (22/32 in the prophylactic group vs. 27/34 in the postintubation group, P = 0.403). CONCLUSIONS: Intravenous injection of 10 mg of dexamethasone was more effective in reducing the severity of POST when administered before tracheal intubation compared with after tracheal intubation.